Enhancing customer retention using customer relationship management approach in car loan bussiness - Simanjuntak, Megawati; Putri, Nadia E.; Yulianti, Lilik N.; Sabri, Mohamad Fazli (Cogent OA, 2020)
The objective of this study was to analyse the effects of customer-perceived value, corporate image, and service quality on customer satisfaction, as well as to analyse the direct effect of switching barriers on customer retention, and to analyse the direct and indirect effects of customer satisfaction on customer retention. The conceptual research framework was examined by subjecting data pertaining to 310 customer car loans to structural equation modelling (SEM). The study findings indicated that customer-perceived value, corporate image, and service quality have a significant effect on customer satisfaction, while switching barriers have a significant effect on customer retention. Although customer satisfaction does not have a significant effect on customer retention, the indirect relationship that occurs through customer trust shows that the trust in the credit process and the service provided will prompt customers to use the company’s products or services when applying for new credit. The managerial implications of these findings include grouping customers, determining sales targets based on customer groups, offering products that have more advantages over competitors, providing credit packages and special programs to promote low-interest rates, and forming telesales as information channels. This research provides an overview of the loyalty of customers that will reuse the previous car loan company when reapplying for credit.